OPTIMALISASI PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS DIGITAL DI TENGAH KETERBATASAN INFRASTRUKTUR SEKOLAH DI SMPN 1 SODONGHILIR - Pemiliani, Puzas; Rukajat, Ajat; Taufik Ismail, Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to examine and formulate strategies for utilizing digital-based learning media amidst the limitations of Information and Communication Technology (ICT) infrastructure at SMPN 1 Sodonghilir. In the era of educational digitalization, the use of technology has become a necessity, yet schools in rural areas are often constrained by limited physical devices and unstable internet networks. The research method used is descriptive qualitative with a case study approach. Data collection was carried out through in-depth interviews with the principal and teachers, observation of the learning process, and documentation of school infrastructure. The results showed that SMPN 1 Sodonghilir implemented several adaptive strategies, including: (1) the utilization of offline-based learning media (such as pre-downloaded interactive digital modules), (2) optimizing the use of students' personal devices (Bring Your Own Device) with a periodic assignment system, (3) implementing flexible blended learning methods, and (4) utilizing digital devices in rotation. The main obstacles faced include limited digital devices, teachers' lack of proficiency in using digital media, poor internet network quality, and electricity availability. These strategies have proven effective in maintaining the continuity of digital-based learning and increasing student engagement in the classroom despite the limitations. This study concludes that teacher creativity and flexibility in school management strategies are key factors in the success of educational digitalization in areas with infrastructure limitations.